Pengaruh Perencanaan Pajak, Beban Pajak Tangguhan, dan Penghindaran Pajak Terhadap Manajemen Laba - Antari Yuliana, Novi; Nuryati, Tutty; Rossa, Elia; Marinda Machdar, Nera (CV. Lafadz Jaya, 2023)
Tax is a source of domestic revenue which is highly expected to exist in supporting state spending and national development. In general, a country that wants to be successful in carrying out its development must be supported by strong funding sources. Therefore, taxes are collected by the government based on law on taxpayers which is an obligation that must be fulfilled by every citizen as a form of participation in the development of their country. The type of data used in this study is quantitative data, namely research that emphasizes testing theories through measuring research variables with numbers and analyzing data using statistical procedures. The results of this study tax planning has no positive and significant effect on earnings management, deferred tax expense has a positive and significant effect on earnings management, tax evasion has a positive and significant effect on earnings management.